MALE SUPERIORITY REPRESENTED THROUGH P.T. BARNUM CHARACTER SCENE IN THE GREATEST SHOWMAN (2017) FILM - Napitupulu, Fitri Any; Fithratullah, Muhammad (Universitas Islam Sumatera Utara, 2024)
This study examines the depiction of male superiority in The Greatest Showman (2017) through the character of P.T. Barnum utilizing Connell’s (2005) framework of hegemonic masculinity to analyze the character of P.T. Barnum. The film serves as a contemporary lens through which to explore the societal constructs of male dominance, ambition, and emotional vulnerability. Despite extensive scholarship on gender dynamics, there remains a notable gap in the cinematic analysis of male superiority, particularly in Western biographical musicals. This study identifies these gaps, specifically in the portrayal of male characters’ internal conflicts and the intersection of personal and professional relationships. Employing a thematic analysis of dialogue and visual elements, the research elucidates how Barnum’s actions reflect traditional masculine ideals while simultaneously challenging them through moments of vulnerability. By examining key dialogues and visual symbols, the findings reveal the complexities of Barnum’s character as both an embodiment of ambition and a critique of rigid masculinity. Ultimately, this research contributes to the broader discourse on gender studies and cinematic analysis, offering insights into how The Greatest Showman both reinforces and complicates contemporary views on masculinity and its implications for societal structures and personal relationships.